BACTERIOLOGICAL STUDIES ON ARABIAN MARES WITH GENITAL INFECTION - M.Al- Shawi, A.; J.N. Al-Shammari , A. (The Iraqi Journal of Veterinary Medicine, 1989)
Out of 111 cervical swabs from Arabian mares, during the period between April 1984 to Feb. 1985, eighty nine bacterial isolates were recovered. Forty five pure bacterial cultures were isolated. These cultures represented: Streptococcus, Styphylococcus, Micrococcus Corynebacterium, Klebsiella, E.coli, Pseudomonus and others.